Association of Social Determinants of Health With Rapid Response Events: A Retrospective Cohort Trial in a Large Pediatric Academic Hospital System - Lawson, Nikki R.; Acorda, Darlene; Guffey, Danielle; Bracken, Julie; Bavare, Aarti; Checchia, Paul; Afonso, Natasha S. (Frontiers in Pediatrics, 2022)
Social determinants of health (SDH) are known to impact hospital and intensive care unit (ICU) outcomes. Little is known about the association between SDH and pediatric rapid response (RR) events and understanding this impact will help guide future interventions aimed to eliminate health disparities in the inpatient setting. The primary objective of this study is to describe the association between SDH and rapid response utilization. The secondary objective is to determine if SDH can predict hospital length of stay (LOS), ICU transfer, critical deterioration (CD), and mortality. A retrospective cohort study was conducted. We reviewed all RR events from 2016-2019 at a large, academic, pediatric hospital system including a level 1 trauma center and two satellite community campuses. All hospitalized patients who had a RR event during their index hospitalization were included. Exposure variables included age, gender, race/ethnicity, language, income, insurance status, chronic disease status, and repeat RR event. The primary outcome variables were hospital LOS, ICU transfer, CD, and mortality. 4568 RR events occurred from 3690 unique admissions and 3301 unique patients, and the cohort was reduced to the index admission. The cohort was largely representative of the population served by the hospital system and varied according to race and ethnicity. Time from admission to rapid response event was longest in non-Hispanic Asian patients and shortest in Hispanic patients. Attending physicians initiated RR calls more in patients identified as non-Hispanic other and least commonly for Hispanic patients. Families who are non-English speaking are also less likely to activate the RR system. LOS was longest for patients speaking languages other than Spanish or English and CD was more common in patients with government insurance. In adjusted logistic regression, Hispanic patients had 2.5 times the odds of mortality compared with non-Hispanic white patients. Disparities exist in access to and within the inpatient management of pediatric patients. Our results suggest that interventions to address disparities should focus on Hispanic patients and non-English speaking patients to improve inpatient health equity. More research is needed to understand and address the mortality outcomes in Hispanic children compared to other groups.